A systematic review on Syrian refugee children with disabilities in Turkiye - Bayrakli, Hatice (Routledge Journals, Taylor & Francis Ltd, 2024)
School-age children constitute a significant portion of the Syrian refugee population in Turkiye. However, the number of studies examining the Syrian refugee children with disabilities (SRCwDs) is very limited. This paper examines intersections of race, disability, and refugee status by providing a systematic review of the available research focusing on SRCwDs residing in Turkiye. After giving contextual information regarding the status of Syrian refugees and presenting research on Syrian refugee children in Turkiye, this paper analyses existing studies on SRCwDs within the theoretical framework of DisCrit. This analysis reveals that research focusing on SRCwDs living in Turkiye is very limited and reliable and comprehensive data is necessary to identify their number in the country. There are also numerous problems regarding their access to services and schooling. Finally, this paper offers recommendations for practice and further research.
Keywords: Syrian refugees; children with disabilities; Dis/Ability Critical Race Theory; Turkiye; intersectionality